Geraldine Ferraro for Vice President Rally at Fresno City College - Watkins, Howard::::::::: (1984)
Congressman Richard Lehman speaking at lectern; Karen Humphrey and Daniel Whitehurst behind him Lectern with Mondale/Ferraro campaign sign and Fresno City College